Is thromboelastography (TEG)-based resuscitation better than empirical 1:1 transfusion?. Issue 1 (8th January 2018) - Howley, Isaac W; Haut, Elliott R; Jacobs, Lenwoth; Morrison, Jonathan J; Scalea, Thomas M
Abstract : Thomboelastography (TEG) is a whole blood measure of coagulation which was originally described in the 1950s. However, it has only been in the last few decades that assays have become accessible and viable as a point-of-care test. Following the observation that hemorrhagic shock is associated with an intrinsic coagulopathy, TEG has been used as a method of diagnosing specific coagulation defects in order to direct individualized blood products resuscitation. An alternative transfusion strategy is the administration of fixed ratio products, a paradigm borne out of military experience. It is unknown which strategy is superior and this topic was debated at the 36th Annual Point/Counterpoint Acute Care Surgery Conference. The following article summarizes the discussants points of view along with a summary of the evidence. Level of evidence: Level III.